Empowering the Marginalized in Tripathi's "Shiva Trilogy": A Foucauldian Perspective - Bhattarai, Krishna Prasad (Vox Batauli, 2023)
The present paper elucidates the portrayal of some Hindu deities in the literary creations of Amish Tripathi. In The Immortals of Meluha, The Secret of the Nagas, and The Oath of Vyauputras, Tripathi portrays the wretched condition of some Hindu gods and goddesses. The study explores the causes behind the subordination of Hindu deities. Replacing the canonical thinking of highlighting the supernatural qualities of deities, those texts expose the hidden realities behind the marginalization of some Hindu deities like, Ganesh, Kali, Sati, and all the Nagas, whose real identity was lying behind the curtain. The spotlight of the present research is to answer the causes of the subordination of major Hindu deities in Tripathi's "Trilogy." This issue is explored with the theoretical parameter of the Foucauldian perspective of power, knowledge, and resistance.